Enhanced production of cellulase from a novel strain Trichoderma gamsii M501 through response surface methodology and its application in biomass saccharification. (December 2020) - Baskaran, Ramiya; Krishnan, Chandraraj
Graphical abstract: Highlights: Isolated a novel T. gamsii M501 producing cocktail of cellulases and xylanases. First of its kind study on biomass saccharification using T. gamsii cellulase cocktail. Saccharification was higher with T. gamsii cellulases than commercial T. reesei cellulases. T. gamsii is useful for on-site cellulase cocktail production in cellulosic ethanol process. Abstract: Cellulolytic enzymes produced by Trichoderma sp. have attracted interest in converting the biomass to simple sugars in the production of cellulosic ethanol. In this work, a novel cellulolytic strain M501 was isolated and identified as T. gamsii by sequencing the ITS rDNA region. The production of cellulase (CMCase) by T. gamsii M501 was enhanced by employing statistical methods. The strain grown in the optimized production medium composed of mineral salts, microcrystalline cellulose (13.7 g/l), tryptone (4.8 g/l) and trace elements (2 mL/l) at pH 5.5 and 28 °C for 72 h produced a maximum CMCase of 61.3 U/mL. The optimized production medium also showed the other enzyme activity of FPU (2.6 U/mL), β-glucosidase (2.1 U/mL), xylanase (681 U/mL) and β- xylosidase (0.6 U/mL). The crude cellulase cocktail produced by T. gamsii M501 efficiently hydrolyzed alkali pretreated sugarcane bagasse with glucose and xylose yield of 78 % and 74 % respectively at 10 % solid loading. This study is the first of its kind research on biomass saccharification using T. gamsii cellulase cocktail. Therefore, the novel strain T. gamsii M501 would be useful for further development of an enzyme cocktail for cellulosic ethanol production.